Charged particle and photon interactions with matter: recent advances, applications, and interfaces - Hatano, Yoshihiko (CRC Press, 2011)
Building on Mozumder’s and Hatano’s Charged Particle and Photon Interactions with Matter: Chemical, Physicochemical, and Biological Consequences with Applications (CRC Press, 2004), Charged Particle and Photon Interactions with Matter: Recent Advances, Applications, and Interfaces expands upon the scientific contents of the previous volume by covering state-of-the-art advances, novel applications, and future perspectives. It focuses on relatively direct applications used mainly in radiation research fields as well as the interface between radiation research and other fields.